G635(P) Regional diabetes awareness education for schools – regional study day. (27th April 2016) - Atkins, M; Drummond, L; Azam, W; Collins, L; McCausland, D; McEwan, R; Orzechowska, A; Peasgood, A; Rumney, C; Sparkes, P; Woods, B
Abstract : With the increase in incidence of Type 1 diabetes in children and young people (CYP) and the use of intensive insulin therapies, paediatric diabetes teams are under increasing pressure to support school staff with the day to day management of their pupils with diabetes. The XX network have developed a study day to provide basic diabetes awareness education to all school staff in the XX region. This work also meets the training and support responsibilities of diabetes teams in line with the statutory guidance for schools governing bodies, 'Supporting Pupils at School with Medical Conditions', (DfE, 2014). The aims of this project have been to provide school staff with an awareness of: All stakeholders responsibilities of managing a CYP with diabetes in school The difference between Type 1 and 2 diabetes Causes, signs and symptoms of diabetes Treatment options How to manage acute complications – hypo and hyperglycaemia Dietary requirements – carbohydrate counting Insulin pump therapy Have a basic understanding of the practicalities of insulin administration and blood glucose/ketone monitoring. To date we have run events, attended by over 270 school staff delegates and attended by over 110 schools in the XX Region. The group believe that this programme can be delivered by any team nationally with minimal need for training and/or explanation in to its use thus minimising development, planning provision and evaluation time. Raising staff awareness of diabetes with school staff, improving their knowledge and confidence around diabetes can only enhance the experience of families with CYP with diabetes when they are dealing with the anxieties of a new diagnosis or a start/change in school/teacher. Parental confidence in the schools capabilities to care for their child throughout the school day is fundamental in both the emotional wellbeing and physical health of the child and parent.